Endocardium gives rise to blood cells in zebrafish embryos - Suman Gurung; Nicole K. Restrepo; Saulius Sumanas (Cell Reports, 2024)
Summary: Previous studies have suggested that the endocardium contributes to hematopoiesis in murine embryos, although definitive evidence to demonstrate the hematopoietic potential of the endocardium is still missing. Here, we use a zebrafish embryonic model to test the emergence of hematopoietic progenitors from the endocardium. By using a combination of expression analysis, time-lapse imaging, and lineage-tracing approaches, we demonstrate that myeloid cells emerge from the endocardium in zebrafish embryos. Inhibition of Etv2/Etsrp or Scl/Tal1, two known master regulators of hematopoiesis and vasculogenesis, does not affect the emergence of endocardial-derived myeloid cells, while inhibition of Hedgehog signaling results in their reduction. Single-cell RNA sequencing analysis followed by experimental validation suggests that the endocardium is the major source of neutrophilic granulocytes. These findings will promote our understanding of alternative mechanisms involved in hematopoiesis, which are likely to be conserved between zebrafish and mammalian embryos.